Snow White with the red hair. 13 - Akiduki, Sorata (Shojo beat manga., 2021)
"Shirayuki is an herbalist with naturally bright-red hair, and the prince of Tanbarun wants her all to himself! She's rescued from her plight by Zen, a prince from the neighboring kingdom ... Shirayuki is headed to Lilias to work as an herbalist and researcher, and she can't hold back the tears when she realizes how much she'll miss everyone. Luckily, Zen knows just what to say to her! And later, Obi makes a stunning confession to Zen."--Provided by publisher